Ribosomal profiling as a tool for studying translation in plants: main results, problems and future prospects - D. A. Afonnikov; O. I. Sinitsyna; T. S. Golubeva; N. A. Shmakov; A. V. Kochetov (Вавиловский журнал генетики и селекции)
The expression of eukaryotic genes can be regulated at several stages, including the translation of mRNA. It is known that the structure of mRNA can affect both the efficiency of interaction with the translation apparatus in general and the choice of translation initiation sites. To study the translated fraction of the transcriptome, experimental methods of analysis were developed, the most informative of which is ribosomal profiling (RP, Ribo-seq). Originally developed for use in yeast systems, this method has been adapted for research in translation mechanisms in many plant species. This technology includes the isolation of the polysomal fraction and high-performance sequencing of a pool of mRNA fragments associated with ribosomes. Comparing the results of transcript coverage with reads obtained using the ribosome profiling with the transcriptional efficiency of genes allows the translation efficiency to be evaluated for each transcript. The exact positions of ribosomes determined on mRNA sequences allow determining the translation of open reading frames and switching between the translation of several reading frames – a phenomenon in which two or more overlapping frames are read from one mRNA and different proteins are synthesized. The advantage of this method is that it provides quantitative estimates of ribosome coverage of mRNA and can detect relatively rare translation events. Using this technology, it was possible to identify and classify plant genes by the type of regulation of their expression at the transcription, translation, or both levels. Features of the mRNA structure that affect translation levels have been revealed: the formation of G2 quadruplexes and the presence of specific motifs in the 5’-UTR region, GC content, the presence of alternative translation starts, and the influence of uORFs on the translation of downstream mORFs. In this review, we briefly reviewed the RP methodology and the prospects for its application to study the structural and functional organization and regulation of plant gene expression.